The Economic Development of Asian Countries With Achievement of SDG 8: A Systematic Literature Review - Alya Dwi Pratiwi; Salahudin Salahudin; Syamsulrizal Syamsulrizal; Havidz Ageng Prakoso (Universitas Ahmad Dahlan, 2023)
This study aims to find the correlation between goal 8 of the Sustainable Development Goals (SDGs) and the economic growth of countries in Asia. This study uses the research method applied in this study, the Systematic Literature Review (SLR), which operates about 600 articles of scientific data sourced from the Scopus database in this review, using the Vosviewer application. The research results reveal many essential points in economic growth in achieving the goals of SDG 8. Since there are still many differences in development that support economic growth, the findings of this study are beneficial to a nation, particularly developing countries in Asia that are still lagging in their economies. With the implementation of the SDGs, the expectation is that the Asian countries are still languishing in infrastructure development as support for the product would realize, and economic growth would be distributed. SDG goal 8,